2019
DOI: 10.24925/turjaf.v7i1.73-80.2123
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Antibacterial and Antioxidant Activity of Nettle (Urtica dioica L.), Mint (Mentha piperita), Thyme (Thyme serpyllum) and Chenopodium album L. Plants from Yaylacık Plateau, Giresun, Turkey

Abstract: Ethanol, chloroform and hexane extracts from plants namely Urtica dioica L., Mentha piperita, Thyme serpyllum and Chenopodium album L. were evaluated for their total phenolic and total flavonoid contents, antioxidant and antibacterial efficiencies. The antioxidant activities were screened utilizing DPPH radical scavenging activity, ABTS scavenging activity, CUPRAC activity and total antioxidant capacity. Antibacterial activity of the tested extracts was determined by disc diffusion and broth dilution methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The study conducted with the CUPRAC method based on the reduction of Cu 2+ to Cu 3+ exhibited the highest antioxidant activity in the ethanol extract of the plant. The ethanol extract exhibited the highest activity in the study by Külcü et al ( 2019 ) using the CUPRAC method. Another study using FRAP indicated that water and methanol extracts of C. album exhibited a good antioxidant activity (Pandey & Gupta, 2014 ).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The study conducted with the CUPRAC method based on the reduction of Cu 2+ to Cu 3+ exhibited the highest antioxidant activity in the ethanol extract of the plant. The ethanol extract exhibited the highest activity in the study by Külcü et al ( 2019 ) using the CUPRAC method. Another study using FRAP indicated that water and methanol extracts of C. album exhibited a good antioxidant activity (Pandey & Gupta, 2014 ).…”
Section: Discussionmentioning
confidence: 79%
“…The study conducted with the CUPRAC method based on the reduction of Cu 2+ to Cu 3+ exhibited the highest antioxidant activity in the ethanol extract of the plant. The ethanol extract exhibited the highest activity in the study by Külcü et al (2019) the antioxidant activities increased and differed depending on the concentration. This difference was associated with factors such as different solvents and extraction methods used, the environment in which the plant was cultivated, and the time of harvesting.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Herbal teas preferred from the most consumed to the least consumed were stinging nettle tea (30.5%), green tea (20.4%), thyme tea (21.6%), linden tea (18.0%), ginger tea (13.2%), and mint tea (1.8%). It has been reported in studies that stinging nettle can be used as a supportive treatment in rheumatic disorders due to its antioxidant and anti-inflammatory properties 17. Theanine, the main amino acid in green tea leaves, has been reported to have significant antistress effects in animals and humans 18.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in studies that stinging nettle can be used as a supportive treatment in rheumatic disorders due to its antioxidant and anti-inflammatory properties. 17 Theanine, the main amino acid in green tea leaves, has been reported to have significant antistress effects in animals and humans. 18 We believe that green tea with low caffeine content reduces the stress of patients and therefore has a positive effect on sleep.…”
Section: Discussionmentioning
confidence: 99%